Comparative characterization of two cxcl8 homologs in oplegnathus fasciatus: genomic, transcriptional and functional analyses - Umasuthan, N.; Bathige, S.D.N.K.; Thulasitha, W.S.; Oh, M.; Lee, J. (University of Jaffna, 2020)
CXCL8 (interleukin-8, IL-8) is a CXC family chemokine that recruits specific target cells and mediates inflammation and wound healing. This study reports the identification and characterization of two cxcl8 homologs from rock bream, Oplegnathus fasciatus. Investigation of molecular signature, homology, phylogeny, and gene structure suggested that they belonged to lineages 1 (L1) and 3 (L3), and designated Ofcxcl8-L1 and Ofcxcl8-L3. While Ofcxcl8-L1 and Ofcxcl8-L3 revealed quadripartite and tripartite organization, in place of the mammalian ELR (Glu-Leu-Arg) motif, their peptides harbored EMH (Glu-Met-His) and NSH (Asn-Ser-His) motifs, respectively. Transcripts of Ofcxcl8s were constitutively detected by Quantitative Real-Time PCR (qPCR) in 11 tissues examined, however, at different levels. Ofcxcl8-L1 transcript robustly responded to treatments with stimulants, such as flagellin, concanavalin A, lipopolysaccharide, and poly(I:C), and pathogens, including Edwardsiella tarda, Streptococcus iniae, and rock bream iridovirus, when compared with Ofcxcl8-L3 mRNA. The differences in the putative promoter features may partly explain the differential transcriptional modulation of Ofcxcl8s. Purified recombinant OfCXCL8 (rOfCXCL8) proteins were used in in vitro chemotaxis and proliferation assays. Despite the lack of ELR motif, both rOfCXCL8s exhibited leukocyte chemotactic and proliferative functions, where the potency of rOfCXCL8-L1 was robust and significant compared to that of rOfCXCL8-L3. The results, taken together, are indicative of the crucial importance of Ofcxcl8s in inflammatory responses and immunoregulatory roles in rock bream immunity.
Keywords: CXC chemokine; CXCL8; Interleukin-8 (il-8); Molecular profiling; Genomic sequence arrangement; Promoter prediction analyses; Transcriptional expression; Chemotaxis; Leukocyte proliferation